Magnetic Resonance Imaging and Bioelectrical Impedance Analysis to Assess Visceral and Abdominal Adipose Tissue - Chaudry, Oliver; Grimm, Alexandra; Friedberger, Andreas; Kemmler, Wolfgang; Uder, Michael; Jakob, Franz; Quick, Harald H.; von Stengel, Simon; Engelke, Klaus (Obesity, 2020)
Objective This study aimed to compare a state-of-the-art bioelectrical impedance analysis (BIA) device with two-point Dixon magnetic resonance imaging (MRI) for the quantification of visceral adipose tissue (VAT) as a health-related risk factor. Methods A total of 63 male participants were measured using a 3-T MRI scanner and a segmental, multifrequency BIA device. MRI generated fat fraction (FF) maps, in which VAT volume, total abdominal adipose tissue volume, and FF of visceral and total abdominal compartments were quantified. BIA estimated body fat mass and VAT area. Results Coefficients of determination between abdominal (r(2) = 0.75) and visceral compartments (r(2) = 0.78) were similar for both groups, but slopes differed by a factor of two. The ratio of visceral to total abdominal FF was increased in older men compared with younger men. This difference was not detected with BIA. MRI and BIA measurements of the total abdominal volume correlated moderately (r(2) = 0.31-0.56), and visceral measurements correlated poorly (r(2) = 0.13-0.44). Conclusions Visceral BIA measurements agreed better with MRI measurements of the total abdomen than of the visceral compartment, indicating that BIA visceral fat area assessment cannot differentiate adipose tissue between visceral and abdominal compartments in young and older participants.
CRIS-Team WoS Importer:2020-01-14